Criminology - Lamarca Pérez, Carmen (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
Criminology is a science that making use of empirical methods studies criminal behavior and the ways in which society reacts. Based on the premise that crime constitutes a social problem, criminology analyzes the factors that may affect and lead to crime, giving special attention to victimology studies and types of social control established to prevent and treat crime.
Keywords: Criminology; crime; delinquent; victim; social control